Analysis of the Impact of E-Wallet Use on Generation Z - Nanda, Resty Meilia; Ranandhea, Adinda; Sudarwati, Anastasia Natalia; Yanti, Nur; Ruliana, Titin (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to identify impulse purchase tendencies in consumers who often see promotions and digital payment options and research on digital wallet applications that are most in demand by Generation Z by University of 17 Agustus 1945 Samarinda. A variety of choices of digital wallet applications that can offer convenience and benefits for users are very much a trend today in the Generation Z era. This study uses a qualitative method where interviews and observations are used as data collection techniques. Based on the observations made, it can be concluded that the use of the DANA digital wallet application by UNTAG Samarinda students, especially in generation Z, increases every year, this is marked by the majority of respondents stating that they have a good experience with the DANA application. The DANA application has an advantage over the Go-Pay digital wallet application, namely the absence of additional administrative fees. Methodology: This study uses natural methods and verbal descriptions in specific contexts through extensive data collection. The respondents in this study are Generation Z students of UNTAG Samarinda with an age range of 18-29 years. Findings: The results of this study show that more people are interested in using the DANA application than Go-Pay than DANA. Limitations/implications: This research has several limitations that need to be developed in the future. First, the research only focuses on Generation Z. Second, this research only uses a comparison of two digital applications, DANA and Go-Pay. Practical implications: This research has several limitations that need to be developed in the future. First, the research only focuses on Generation Z. Second, this research only uses a comparison of two digital applications, DANA and Go-Pay. Originality/value: This research can be applied to consumers, businessmen, and business merchants. Paper type: General review